2020
DOI: 10.1016/j.drup.2020.100691
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein isoforms as double agents – Their roles in carcinogenesis, cancer progression and chemoresistance

Abstract: Metallothioneins (MTs) are small cysteine-rich intracellular proteins with four major isoforms identified in mammals, designated MT-1 through MT-4. The best-known biological functions of MTs are their ability to bind and sequester metal ions and their active role in redox homeostasis. Despite these protective roles, numerous studies have demonstrated that changes in MT expression could be associated with the process of carcinogenesis and participation in cell differentiation, proliferation, migration, and angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 214 publications
(251 reference statements)
0
27
0
Order By: Relevance
“…Metallothioneins (MTs) are a phylogenetically conserved family of low molecular weight (6–7 kDa) single-chained and cysteine-rich proteins [ 1 , 2 , 3 ]. In humans, there are four major isoforms of MTs, encoded by clustered genes at chromosome 16q12-22 and identified as MT-I to MT-IV [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metallothioneins (MTs) are a phylogenetically conserved family of low molecular weight (6–7 kDa) single-chained and cysteine-rich proteins [ 1 , 2 , 3 ]. In humans, there are four major isoforms of MTs, encoded by clustered genes at chromosome 16q12-22 and identified as MT-I to MT-IV [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metallothioneins (MTs) are a phylogenetically conserved family of low molecular weight (6–7 kDa) single-chained and cysteine-rich proteins [ 1 , 2 , 3 ]. In humans, there are four major isoforms of MTs, encoded by clustered genes at chromosome 16q12-22 and identified as MT-I to MT-IV [ 1 ]. MT-I and MT-II show a high degree of sequence matching and are commonly co-regulated, being considered as one functional unit denoted as MT I/II and usually referred as MTs in the narrow sense [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, it has been shown that MTs overexpression is associated with chemoresistance and poor prognosis in a variety of cancers [ 2 ]. Recently, several studies found that resistance to apoptogenic agents is common in cancers that overexpress MTs [ 78 , 79 ].…”
Section: Metallothioneins Regulates Lysosomal Function In Cancer Cmentioning
confidence: 99%
“…Many factors are known to influence the development of secondary resistance, such as the genetic changes of cancer cells, the rate of tumor growth, but also the effects of the microenvironment, e.g., hypoxia which is well known to induce chemo- and radio-resistance [ 2 ]. In the last decades, mechanisms of resistance are intensively investigated, the most well-known ones being: (i) increased drug efflux from the cancer cells or decreased drug entrance to the cancer cells; (ii) downregulation, overexpression, or modification of target molecule(s); (iii) changes in drug activating and ⁄or detoxifying enzymes; (iv) the induction of anti-apoptotic mechanisms or the inactivation of pro-apoptotic mechanisms; (v) decreased access of drug to the target cellular compartments (usually nucleus); (vi) alteration of the cell cycle (most cells move to the G 0 phase when sensitivity to the majority of cytostatics is low); (vii) pharmacological and physiological factors, such as changes in drug metabolism and excretion, and inadequate access of the drug to the tumor including blood brain barrier in brain tumors; and (viii) also microenvironment plays a role in chemoresistance by the production of stimulating factors that induce survival pathways and it also may inactivate drugs [ 1 , 2 , 3 , 4 ]. In addition, a number of studies have revealed the importance of metallothioneins (MT) for the defense mechanisms of tumor cells against the effect of chemotherapy by preventing apoptosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%